2005
DOI: 10.1115/1.1787510
|View full text |Cite
|
Sign up to set email alerts
|

Rich-Catalytic Lean-Burn Combustion for Low-Single-Digit NOx Gas Turbines

Abstract: A new rich-catalytic lean-burn combustion concept (trademarked by PCI as RCL) was tested at industrial gas turbine conditions, in Solar Turbines’ high-pressure (17 atm) combustion rig and in a modified Solar Turbines engine, demonstrating ultralow emissions of NOx<2 ppm and CO<10 ppm for natural gas fuel. For the single-injector rig tests, an RCL catalytic reactor replaced a single swirler/injector. NOx<3 ppm and CO<10 ppm were achieved over a 110°C operating range in flame temperature, including N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(11 citation statements)
references
References 17 publications
0
11
0
Order By: Relevance
“…In particular, much effort is devoted to the reduction of NO x emissions and increase of safety and efficiency in natural gas combustion appliances at both the industrial and domestic level. To date, improvements in gas turbine and utilities burners have resulted in an impressive reduction in NO x emissions by using lean-premixed combustion of natural gas (Smith et al, 2005). Further potential improvements are foreseen with premixed catalytic combustion technology (Forzatti, 2003), which can indeed guarantee the lowest NO x emissions compared to other combustion options (Specchia, 2006) while enhancing the heat transfer efficiency through radiation.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…In particular, much effort is devoted to the reduction of NO x emissions and increase of safety and efficiency in natural gas combustion appliances at both the industrial and domestic level. To date, improvements in gas turbine and utilities burners have resulted in an impressive reduction in NO x emissions by using lean-premixed combustion of natural gas (Smith et al, 2005). Further potential improvements are foreseen with premixed catalytic combustion technology (Forzatti, 2003), which can indeed guarantee the lowest NO x emissions compared to other combustion options (Specchia, 2006) while enhancing the heat transfer efficiency through radiation.…”
Section: Introductionmentioning
confidence: 97%
“…In recent years, fuel-rich catalytic=homogeneous combustion technology has been proposed to overcome the limitations of lean premixed catalytic and non-catalytic combustion due to its potential benefits in terms of improved safety and stability of operation, associated to ultra low pollutants emissions (Forzatti, 2003;Pfefferle et al, 2006;Smith et al, 2005). Recently we have extended the concept of fuel-rich catalytic combustion by proposing a novel staged hybrid catalytic gas burner, with integrated interstage heat removal by IR radiation from the catalytic module (Accordini et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…The major source of GTU pollutant emissions is an exhaust device, which releases combustion products (nitrogen oxides, sulfur dioxide, carbon monoxide, hydrocarbons, suspended solids) to the atmosphere. The assessments of nitrogen oxide and dioxide concentration fields considering their background values point out the necessity of suppressing the nitrogen oxides in some sites using denox technology (stands for the word combination "de NO x ") [7]. This technology involves the injection of desalinated water into the GTU combustion chamber.…”
Section: Operation Stage Of the Mgtppmentioning
confidence: 99%
“…Results from work with Solar Turbines, Incorporated (Karim et al, 2003;Smith et al, 2005) showed NOx emissions as low as 1 ppm were achievable in rig tests, while the engine tests showed NOx emissions around 2 ppm, both with CO below 10 ppm. The engine test also demonstrated excellent RCL ® reactor operability through the entire range of engine operating conditions, including transient events such as start-up, shutdown, and load shifting.…”
Section: The Rclmentioning
confidence: 99%
“…The RCL ® system is based on the concept of stabilizing combustion with catalytically-reacted fuel and air having a temperature below the instantaneous autoignition temperature (Smith et al, 2005). PCI's RCL ® system is shown schematically in Figure 1.…”
Section: Introductionmentioning
confidence: 99%